Ichthyofauna Checklist in Tributaries of Muda Reservoir, Kedah, Peninsular Malaysia - Nor Aziella Mohd Rosli; Nurul Shafikah Mohd Noor; Khaironizam Md Zain (Indonesian Journal of Limnology, 2021)
Ichthyofauna checklist was scrutinized in tributaries of Muda Reservoir. A total of 5998 specimens were caught using a cast net of 2.5 cm mesh size. Amongst these specimen, 30 fish species from 12 families were recorded. The most dominant fish family in this lotic ecosystem was Cyprinidae. Rasbora dusonensis, Cyclocheilichthys apogon and Mystacoleucus marginatus recorded the uppermost distribution compared to other fish species found in this tributaries. Six fish species were the newly recorded species found in tributaries of Muda Reservoir; Barbonymus gonionotus, Luciosoma setigerum, Toxabramis houdemeri, Mystus singaringan, Anabas testudineus and Trichopodus pectoralis. In accordance with the previous combination of recorded fish species in tributaries of Muda Reservoir, a total of 57 updated total numbers of fish species were recorded. The information obtained in present study will update the latest ichthyofauna checklist in tributaries of Muda Reservoir, as well as for the future comparison in other geographical locations.